ANALISIS PEMANFAATAN DAN PENGOLAHAN KELAPA KOPRA PUTIH OLEH PETANI DESA BAGAN JAYA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI ERA PANDEMI COVID 19 - Soniati; ANDRIANSYAH (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2021)
The purpose of this research is to determine the utilization and processing of white copra coconut and the income of farmers in managing coconut into copra and to analyze the added value that can be created by managing coconut into copra. This research has been carried out in Bagan Jaya Village, Enok District, Indragiri Hilir Regency. The determination of the research location was carried out intentionally (porposively) with the consideration that Bagan Jaya Village is one of the coconut production centers. The time of conducting the research starts from August 7 to September 23, 2021. The analysis used is the Analysis of Income and Value added. The results showed that the average income obtained by coconut farmers from the sale of copra was Rp. 17,000,000